Ancient Water Technologies, by Larry W. Mays (Ed.), 2010. Springer, Dordrecht/Heidelberg/London/New York. 280 pages. Hardback: price 159.99, ISBN 978-90-481-8631-0; paperback: price 149.99, ISBN 978-94-007-9336-1. - Szczepaniak, Małgorzata (Geologos, 2018)
[Missing]